A Study on the National Drug Policies of Bangladesh to Ensure Health for All - Rahman, Md Aknur; Hossain, Md Riaz; Hossain, Md Aslam; Amran, Md Shah (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Bangladesh approved the proposal for a National Drug Policy on May 29, 1982. We know that such drug policies are developed gradually over a period of time and may contain a lot of comprehensive documents. But in Bangladesh, the expert committee worked out the policy, based on 16 standards within 15 days. This vital document, almost unchanged, was made a law on 12 June 1982. A few years later, it can be observed that despite opposition from many concerns, the output of essential drugs has increased from about 30 to about 80 percent, prices have in almost all cases gone down considerably, the domestic industry has grown rapidly, the quality of its production has increased dramatically, and people’s awareness about quality medicines has been steadily growing. The World Health Organization (WHO) has stressed the need of a formulated drug policy in every country of the world in 1986. Bangladesh responded very early to this respect. Subsequently, two more national drug policies were promulgated in 2005 and 2016 respectively. Experience over the decades has shown that the said policies could not fulfill the declared objective of ensuring health for all. Our aim is to describe some of the lacunae for which total implementation of drug policy is still struggling. To find the root causes, a total of five hundred volunteers were surveyed by supplying a questionnaire on drug policy. It was observed that most of the participants opined that the incumbent government needs to be more stringent to implement the drug policy into reality by utilizing the public servants and public sectors, especially health personnel to ensure health for all. Dhaka Univ. J. Pharm. Sci. 20(1): 41-48, 2021 (June)